2011
DOI: 10.1007/s10811-011-9690-3
|View full text |Cite
|
Sign up to set email alerts
|

Designed optimization of a single-step extraction of fucose-containing sulfated polysaccharides from Sargassum sp.

Abstract: Fucose-containing sulfated polysaccharides can be extracted from the brown seaweed, Sargassum sp. It has been reported that fucose-rich sulfated polysaccharides from brown seaweeds exert different beneficial biological activities including anti-inflammatory, anticoagulant, and anti-viral effects. Classical extraction of fucose-containing sulfated polysaccharides from brown seaweed species typically involves extended, multiple-step, hot acid, or CaCl 2 treatments, each step lasting several hours. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 31 publications
(55 reference statements)
3
72
0
Order By: Relevance
“…The solubilization yields decreased with temperatures in the range tested, a fact ascribed to the instability of fucose-containing compounds under harsh conditions [6]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solubilization yields decreased with temperatures in the range tested, a fact ascribed to the instability of fucose-containing compounds under harsh conditions [6]. …”
Section: Resultsmentioning
confidence: 99%
“…Due to their non-toxic character, fucoidans have been recently explored for medicinal properties, but their detailed structural analysis is complex [11], and the structure–activity interrelationships are not yet clear [6,12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acid concentration did not have a significant effect on fucose level. Ale, Mikkelsen and Meyer [26] reported that 0.03 M HCl was the optimal concentration for extraction of fucose containing sulphated polysaccharides from Sargassum sp.…”
Section: Effect Of Independent Variables On Bioactive Compoundsmentioning
confidence: 99%
“…In addition to sulfate these backbone residues may be substituted with fucosides, single fucose substitutions, and/or glucuronic acid, xylose or glucose substitutions [21]. The compositional and structural features of FCSPs differ significantly among seaweed species and that these features are markedly influenced by the conditions used to extract them [20,23]. Fucoidan extracted from brown seaweed algae Fucus vesiculosus [24], Ascophyllum nodosum [25], Sargassum kjellmanianum [26], Sargassum thunbergii [27], Cladosiphon okamuranus Tokida [28], in which the percentage of L-fucose ranged from 12.6 to 36.0 %, and the percentage of sulfate content from 8 to 25 %.…”
Section: Structure and Composition Of Fucoidanmentioning
confidence: 99%